Identification of functional variants in the Alzheimer’s disease candidate gene ABCA7 - Clement, Naomi Susan (2017)
Late onset Alzheimer’s disease (LOAD) is the commonest form of dementia, affecting approximately 850,000 patients in the UK alone, predicted to exceed one million by 2025. The cause of LOAD is complex, but several large Genome Wide Association Studies have highlighted 21 genetic loci associated with this devastating disease and the ATP-Binding Cassette Protein, family A, member 7 (ABCA7) is one of these genetic loci. However, the exact reasons behind this association are still unknown, focusing work on identifying functional, pathogenic mutations within this locus.